They are Coming - Mlalazi, Christopher (Book collections on Project MUSE., 2014)
This is the story of a small family in Lobengula township, Bulawayo: a shoemaker, Ngwenya, his wife, MaVundla, and their two children, Ambition and Senzeni, whose lives are turned upside-down when Senzeni joins the local youth militia. Mlalazi captures the texture of everyday life in the township, the humour, warmth, rivalry and fear as neighbours interact with each other or get swept up by events outside their control. Their constant search, however, is for autonomy and independence, for the ability to have control over their own lives. They are Coming provides us with perspectives often hidden from view, in a story where particular events are part of a more complex history.